Sprachliche und grafische Gestaltung der Schlagzeilen zum Thema Coronavirus in der Online-Boulevardpresse im Deutschen und im Polnischen - Justyna Duch-Adamczyk (Linguistische Treffen in Wrocław, 2023)
In this article, selected headlines on the topic of coronavirus in the German and Polish online tabloid press will be analysed and described. The aim is to shed light on linguistic and graphical characteristic of the headlines examined as well as to show differences and similarities in the design of the headlines in the two languages. The following text presents press headlines from two online sources – the Bild newspaper and Superexpress (bild.de and se.pl). Based on the collected material the author discusses the following phenomena: graphic distinctions, noun accumulations, exclamations, questions in the headline, as well as the area of evaluating vocabulary. The used phenomena attract the reader’s attention and encourage to read. It is also not without significance that the issues discussed evoke emotions and feelings of fear, anxiety and uncertainty in the reader, which accompany the epidemic situation. The article ends by summarising the analysis and pointing out the differences between the two languages and styles.